Skin Game’s Storytelling Strategy in Building Brand Image as a Basic Skincare for Indonesian Skin - Nirwasita Fathinah Maharani; Muhammad Aras (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Storytelling has emerged as a central strategy in digital brand communication, particularly in the skincare sector, where building consumer trust and brand image is essential. However, prior studies have been predominantly quantitative and focused on consumer perspectives, leaving a gap in qualitative exploration from the brand’s standpoint in local contexts. Objective: This research focuses on Skin Game as one of Indonesia’s local skincare brands through the lenses of Narrative Theory, Narrative Paradigm, and Rhetorical Theory in examining how the brand uses storytelling to build its image and corporate reputation. This study examines the brand storytelling strategies of Skin Game, a local Indonesian skincare brand, through the integrated lenses of Narrative Theory, Narrative Paradigm, and Rhetorical Theory to understand how storytelling constructs brand image and reputation. Methods: A qualitative exploratory case study design was employed, combining semi-structured interviews with four key informants and content analysis of Skin Game’s Instagram, TikTok, and official website from February 2024 to August 2025. Results: Findings reveal that Skin Game constructs its brand identity through local relevance, educational content, and emotional intimacy, delivered via personal language, minimalist visuals, and inclusive representation of tropical skin. These narrative strategies strengthen authenticity and consumer trust, reinforcing its positioning as a Basic Skincare Expert. Conclusion: Storytelling functions as a strategic communication practice that enables local brands to build emotional connections, credibility, and long-term brand equity. The integration of narrative and rhetorical frameworks provides actionable insights for developing authentic, sustainable marketing strategies in competitive local markets.